Proceedings of the 27th ACM Conference on on Innovation and Technology in Computer Science Education Vol. 1 2022
DOI: 10.1145/3502718.3524764
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Learner Resilience and Performance of First-Year Computer Science Undergraduate Students during the COVID-19 Pandemic

Abstract: This paper presents the findings from a research project exploring the impact of learner resilience as part of the shift to online delivery of learning, teaching and assessment amidst national social "lockdown" measures as a result of the COVID-19 pandemic. This exploration of resilience was undertaken as part of the delivery of a first-year undergraduate computer science degree programme in a UK higher education institution over two academic years. Resilience was measured by the Nicholson McBride Resilience Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
2
3
0
Order By: Relevance
“…Again, early level students were more negatively impacted than their senior peers, reporting more issues with technology and even a slightly worse learning experience in 2021. This aligns with existing literature on the correlation between student level and performance in online learning [11,21,28,29], as well as with our previous study. We have also confirmed that students enrolled in courses delivered asynchronously find it more difficult to ask questions in class, as well as participating in laboratories.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Again, early level students were more negatively impacted than their senior peers, reporting more issues with technology and even a slightly worse learning experience in 2021. This aligns with existing literature on the correlation between student level and performance in online learning [11,21,28,29], as well as with our previous study. We have also confirmed that students enrolled in courses delivered asynchronously find it more difficult to ask questions in class, as well as participating in laboratories.…”
Section: Discussionsupporting
confidence: 92%
“…Raju et al [20] found that CS students had a comparable or even worse attitude toward online learning than non-CS students. Crick et al [21] reported that first year CS students struggled more than their older peers with the online learning format, which aligns with the results of our previous study [6]. In particular, first year students seemed more inclined to rely on themselves when facing difficulties, instead of seeking help or trying to engage with peers or instructors, with negative effects.…”
Section: Impact Of Covid-19 On Higher Educationsupporting
confidence: 89%
See 1 more Smart Citation
“…Other peer assessment schemes may be employed to assess a combination of dispositions and skills in team working contexts [37,66,67]. Self assessment of aspects of positive psychology may also be used to address some learner dispositions [65,69,192,198]. As stated earlier, a single demonstration of a task is typically insufficient to demonstrate that learners repeatedly and over an extended period apply necessary skills with an appropriate disposition.…”
Section: Assessing Dispositionsmentioning
confidence: 99%
“…With learners who purport to be increasingly digitally confident and capable now entering higher education, academics may need to reconsider their approaches to learning, teaching and assessment strategies. As student performance is dependent on attentional engagement, it is crucial to identify and mitigate potential distractions that might capture attention and undermine performance [3,6,7]. To improve attention, practitioners have considered aspects such as activity timings [5], or the role of the teacher [1],…”
mentioning
confidence: 99%